2018
DOI: 10.1088/1361-6404/aae3ce
|View full text |Cite
|
Sign up to set email alerts
|

The Modelling Framework for Experimental Physics: description, development, and applications

Abstract: The ability to construct, use, and revise models is a crucial experimental physics skill. Many existing frameworks describe modeling in science education at introductory levels. However, most have limited applicability to the context of upperdivision physics lab courses or experimental physics. Here, we discuss the Modeling Framework for Experimental Physics, a theoretical framework tailored to labs and experimentation. A key feature of the Framework is recursive interaction between models and apparatus. Model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 50 publications
0
25
0
1
Order By: Relevance
“…The overarching goals of using AR technology in this manner were to reduce students' extraneous processing and to promote the construction of conceptual knowledge by providing contiguous information (Dounas‐Frazer & Lewandowski, ; Kuhn et al ., ; Lai, Chen, & Lee, ; Strzys, Thees, Kapp, & Kuhn, ; Thees et al ., under review).…”
Section: Introductionmentioning
confidence: 99%
“…The overarching goals of using AR technology in this manner were to reduce students' extraneous processing and to promote the construction of conceptual knowledge by providing contiguous information (Dounas‐Frazer & Lewandowski, ; Kuhn et al ., ; Lai, Chen, & Lee, ; Strzys, Thees, Kapp, & Kuhn, ; Thees et al ., under review).…”
Section: Introductionmentioning
confidence: 99%
“…1) in physics laboratory courses and clinical settings at the University of Colorado Boulder [11,13,[25][26][27][28]. For a detailed summary of the development and applications of the Modeling Framework, see Ref [29].…”
Section: B Research On the Modeling Frameworkmentioning
confidence: 99%
“…These students reported that they learned how to model but offered no further reflections, and they were able to identify some limitations of their models. There are two possible explanations: the lack of student responses related to modeling may be because that the students did not understand what the instructor wanted them to reflect upon; the lack of depth in reflection on modeling signifies that, as instructors, we can do a much better job supporting students thinking about modeling and developing their modeling skills such as by using the Modeling Framework for Experimental Physics [18,19].…”
Section: Experiences With Modelingmentioning
confidence: 99%